Improvement of PD-1 Blockade Efficacy and Elimination of Immune-Related Gastrointestinal Adverse Effect by mTOR Inhibitor - Bai, Xin; Wang, Xueyan; Ma, Guozhen; Song, Jinen; Liu, Xiaowei; Wu, Xi; Zhao, Yujie; Liu, Xu; Liu, Zhihui; Zhang, Wei; Zhao, Xin; Zheng, Zirui; et al. (Frontiers in Immunology, 2021)
During the past decades, immunotherapy, especially the antibody-mediated immune checkpoint blockade (ICB) has shown durable tumor inhibition and changed the paradigm of cancer treatment. However, a growing body of evidence suggests that ICB treatment induces severe immune-related adverse events (irAEs), and the side effect even leads to the discontinuation of lifesaving treatment. Here, we found that ICB treatment induces colitis in melanoma patients and promotes the infiltration of CD8+ effector T cells into colitic lesions. Further transcriptomic dissection indicated the PI3K-AKT-mTOR pathway was highly activated in CD8+ effector T cells of colitic lesions. Moreover, we developed a mouse melanoma model to recapitulate the gastrointestinal toxicity of anti-PD-1 treatment in clinical settings. Anti-PD-1 treatment significantly contributed to the infiltration of CD8+ T cells, and correspondingly induced severe enteritis. Immunohistochemistry experiments showed that the PI3K-AKT-mTOR pathway of T cells was activated by anti-PD-1 treatment. Blockade of the pathway with mTOR inhibitor sirolimus not only inhibits tumor growth but also suppresses the T cell infiltration in colitic lesions. More importantly, combination with sirolimus and anti-PD-1 synergistically inhibits tumor growth via inducing the immunogenic cell death of tumor cells in vivo. In summary, our research demonstrated the principle of mTOR inhibitor and anti-PD-1 combinatorial therapeutic regimen, which provided a novel therapeutic strategy for irAEs in clinics.